IN PROGRESSING POPULATION ENTREPRENEURSHIP AND ENTREPRENEURIAL CULTURE - A REPLACEMENT OF ECONOMIC BEHAVIOR (World Economics and Finance Bulletin, 2024)
In this article, the population depends on the economic culture in raising the business mindset, and the economic behavior of the population as a whole system is effectively covered. It has been scientifically analyzed that economic culture, production culture is a whole social system, and its use is effective only if it is implemented in a complex way.
Keywords: Population; research; competitive